Methodology of Political Management in Teaching Modern Political Science - Seydabullaeva Tangirbergenovna (Penerbit Jurnal Indonesia, 2024)
In contemporary political practice, political management has become one of the most popular and effective methods of governance. As a flexible and practical form of political influence, it is increasingly utilized by political organizations, parties, and government officials worldwide. However, its fundamental role in applied political science education is often overlooked. Tracing its origins to state institutions rather than commerce, political management is rooted in the early practices of governmental administration, exemplified by the work of F.W. Taylor in the early 20th century. This paper explores the role of political management within the political system, outlining its types and methodologies. Emphasis is placed on understanding political governance as a mechanism for influencing public life, while the article also highlights modern methods such as quantitative and qualitative empirical approaches, and theoretical methods including systemic, structural-functional, and critical-dialectical analysis. Political management's significance and application in modern political systems are examined through both theoretical frameworks and practical experiences.